401 MHz transistorised radiosonde transmitter - SRIVASTAVA, S. K.; BINDRA , S. K.; BHARDWAJ, M. P. (MAUSAM, 1992)
This paper describes a transistorised radiosonde transmitter which was designed to replace valve version earlier used in national upper air l1etwork for upper air data acquisition. The transmitter operates in 400.6-406 MHz frequency band (tunable) with 500 mill watt power output utilising a 22.5V water activated battery, Stripling technique has been deployed to obtain the optimum. design and transmitted meets all the stringent requirements laid down for accurate data conversion and transmission. The system IS In routine use In the national upper air network and the performance is satisfactory.